Acculturation in Chang-rae Lee’s Native Speaker - Kohlová, Petra (American & British Studies Annual, 2022)
This article explores acculturation strategies and their expressions in the novel Native Speaker (1995) by Chang-rae Lee, a Korean-American author. This novel concerns the clash of immigrant identities with the notion of a genuinely American identity as well as the adaptation into the majority society by first- and second-generation immigrants. While this is not Lee’s first novel concerned with intricate identity issues, Native Speaker is considered his most important work, as it introduced Korean-American fiction to the U.S. mainstream public. Although the novel is well known to critics, it has not been analysed using the particular view of acculturation strategies featured here which deal with psychological and intercultural relations of individuals in their private and public lives. The notion of acculturation used here is based on the well-known model proposed by psychologist John W. Berry, a paradigm consisting of four strategies: assimilation, integration, separation, and marginalization. This view argues that, despite coming from similar ethnic backgrounds, the plethora of characters each engage with the U.S. mainstream differently (in their public and private lives), thus their acculturation categories may also change through time. This is exemplified through changes in the protagonist Henry Park.